PEMBUATAN VIDEO PROFIL OBJEK WISATA GOA SIMULLUK UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN LEMBANG TONDON MATALLO - Garonga, Melki; Lura, Hans; Limbong, Irianto Rante (STKIP Persada Khatulistiwa Sintang, 2024)
ABSTRACTOne of the implementations of the tridarma of higher education is community service. Thematic Real Work Lecture (KKN-T) is a form of service activity from a person or group of students to the community. Students who are included in it are followed by cross-vocational. In the implementation of the Thematic Real Work Lecture (KKN-T), several problems were found among the community including tourism, education and government. This Thematic KKN raised one of the themes determined from the campus, namely